The Sloan Digital Sky Survey Reverberation Mapping Project: Key Results - Shen, Y; Grier, CJ; Horne, K; Stone, Z; Li, JI; Yang, Q; Homayouni, Y; Trump, JR; Anderson, SF; Brandt, WN; Hall, PB; Ho, LC; et al. (American Astronomical Society, 2024)
We present the final data from the Sloan Digital Sky Survey (SDSS) Reverberation Mapping (RM) project, a precursor to the SDSS-V Black Hole Mapper RM program. This data set includes 11 yr photometric and 7 yr spectroscopic light curves for 849 broad-line quasars over a redshift range of 0.1 < z < 4.5 and a luminosity range of L bol = 1044−47.5 erg s−1, along with spectral and variability measurements. We report 23, 81, 125, and 110 RM lags (relative to optical continuum variability) for broad Hα, Hβ, Mg ii, and C iv using the SDSS-RM sample, spanning much of the luminosity and redshift ranges of the sample. Using 30 low-redshift RM active galactic nuclei with dynamical-modeling black hole masses, we derive a new estimate of the average virial factor of logf=0.62±0.07 for the line dispersion measured from the rms spectrum. The intrinsic scatter of individual virial factors is 0.31 ± 0.07 dex, indicating a factor of 2 systematic uncertainty in RM black hole masses. Our lag measurements reveal significant R–L relations for Hβ and Mg ii at high redshift, consistent with the latest measurements based on heterogeneous samples. While we are unable to robustly constrain the slope of the R–L relation for C iv given the limited dynamic range in luminosity, we found substantially larger scatter in C iv lags at fixed L 1350. Using the SDSS-RM lag sample, we derive improved single-epoch (SE) mass recipes for Hβ, Mg ii, and C iv, which are consistent with their respective RM masses as well as between the SE recipes from two different lines, over the luminosity range probed by our sample. The new Hβ and Mg ii recipes are approximately unbiased estimators at given RM masses, but there are systematic biases in the C iv recipe. The intrinsic scatter of SE masses around RM masses is ∼0.45 dex for Hβ and Mg ii, increasing to ∼0.58 dex for C iv.